2018
DOI: 10.1177/1753944718803309
|View full text |Cite
|
Sign up to set email alerts
|

Remote post-conditioning and allopurinol reduce ischemia-reperfusion injury in an infra-renal ischemia model

Abstract: Background:The aim of this study was to evaluate the effects of the antioxidant allopurinol and ischemic post-conditioning on the deleterious effects of ischemia followed by reperfusion (I/R) in a standardized model of ischemia involving infra-renal aortic occlusion in rats.Methods:The animals were randomly divided into five groups: (A) animals not subjected to ischemia; (B) animals subjected to 2 h of ischemia and reperfusion only once; (C) animals given an allopurinol dose by gavage, then subjected to 2 h of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The literature reviewed showed that several authors have reported results in agreement with those described here. They conclude that when allopurinol is administered, the effect on the prevention of IRI is only significant in those cases in which this treatment is associated with ischemic postconditioning, that is, periods of arterial reocclusion of a few minutes duration applied at the beginning of tissue reperfusion and which have shown a decrease in the damage associated with ROS [31,32]. In contrast, there are also studies in which its oral administration prior to ischemia instauration does demonstrate an antioxidant effect, as evidenced by a reduction in HID and a decrease in the production of oxidative stress markers such as malondialdehyde (MDA) [33].…”
Section: Discussionmentioning
confidence: 99%
“…The literature reviewed showed that several authors have reported results in agreement with those described here. They conclude that when allopurinol is administered, the effect on the prevention of IRI is only significant in those cases in which this treatment is associated with ischemic postconditioning, that is, periods of arterial reocclusion of a few minutes duration applied at the beginning of tissue reperfusion and which have shown a decrease in the damage associated with ROS [31,32]. In contrast, there are also studies in which its oral administration prior to ischemia instauration does demonstrate an antioxidant effect, as evidenced by a reduction in HID and a decrease in the production of oxidative stress markers such as malondialdehyde (MDA) [33].…”
Section: Discussionmentioning
confidence: 99%
“…Gholampour et al treated [37] with remote ischemic perconditioning and quercetin which reduced plasma AST activity in the liver after renal I/R. Brandão et al observed [38] separately the protective effects of allopurinol and the benefits of ischemic post-conditioning by measuring ASTl with significantly reduced I/R systemic injuries in rats.…”
Section: Discussionmentioning
confidence: 99%
“…"Ischemia" is defined as the loss of blood flow by depriving a tissue of metabolic substrates such as glucose as a result of reduced blood flow and impaired nutrition. "Reperfusion" is used to describe the restoration of blood flow and tissue nutrition after a period of ischemia and is a critical step in dealing with any ischemia condition 1,2 . Ischemia is associated with progressive decline in cellular functions, increased oxidative and inflammatory response.…”
Section: Introductionmentioning
confidence: 99%